Sucka 4 luv - Pierre, Patrick (Film director); Dunning, Ashley; McKnight, Samuel (Actor); Horton, William "Spank"; Pierre Films LLC; Leomark Studios (Firm) ([Los Angeles, CA] : Pierre Films LLC, 2014)
The film is about a young man with an anger management problem who wants to marry his longtime girlfriend. The clever girlfriend knows all too well how much he loves, but she's devised a formula to assist him in getting over his anger problems. She decides to put him on a 30-day anger free boot camp. Will beauty tame his inner beast? The boot camp consists of her putting him in very stressful situations seeing if he will lose his cool. Some of the situations include her going out on several dates with many strange men and forcing him to be a witness to the dates. If he can survive the 30 days of "love" boot camp without once losing his cool, she promises to marry him. Trust, patience, understanding, temperance, and faith will be tested. Will the boyfriend survive this 30-day anger fast? Only time will tell.
Originally released as a motion picture in 2014.
William "Spank" Horton, Xavia Omega, Cary Hite, Lawrence Killebrew, Frika Lynn Gressen, Janice McDuffy, Darrah Lashley.
Cinematographer, Hiu Kwong Yau ; editors, Jamaal Green, Patrick Pierre ; music, Rick Meale.
In English with optional English subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed July 8, 2016).
Keywords: subject -- Drama; Feature films; Internet videos; Streaming video